A educação do Movimento dos Sem-Terra: Instituto de Educação Josué de Castro - Dal Ri, Neusa Maria [UNESP]; Vieitez, Candido Giraldez [UNESP] (Centro de Estudos Educação e Sociedade - Cedes, 2004)
The Instituto de Educação Josué de Castro (Institute of Education Josué de Castro), sponsored by the Instituto Técnico de Capacitação e Pesquisa da Reforma Agrária (Technical Institute for Training and Research in Agrarian Reform) which is associated to the Movimento dos Sem-Terra (MST - Landless Farm-worker Movement), provides both secondary education and technical training. This paper aims at describing the features of this school and at elucidating whether its educational conception, which seems to be similar to that of the schools controlled by the MST, presents educational characteristics that may be of interest for the working classes as a whole, from a democratic and popular point of view. The investigation showed that the Instituto, whose framework and organization differ from those usually found in official schools, emphasizes such educational categories as the union between teaching and work, and a management democratically shared among students, teachers and school staff.

O Instituto de Educação Josué de Castro, que tem como mantenedor o Instituto Técnico de Capacitação e Pesquisa da Reforma Agrária e é vinculado ao Movimento dos Sem-Terra, constitui-se em uma escola de educação média e profissional. O objetivo deste texto é o de expor os elementos educativos principais presentes na escola, bem como elucidar se a sua concepção educacional, que parece ser a mesma vigente nas escolas controladas pelo MST, contém elementos educacionais de interesse para as classes trabalhadoras em geral, do ponto de vista democrático e popular. A investigação revelou que o Instituto, estruturado e organizado de forma diferente daquela usualmente encontrada nas escolas oficiais, coloca em epígrafe categorias educacionais como a união do ensino com o trabalho e a gestão democrática compartilhada entre alunos, professores e funcionários.
The education of the Landless Farm-worker Movement: Institute of Education Josué de Castro
Keywords: Education; Work; Self-management; Educação; Trabalho; Autogestão